Marrow Infiltrating Lymphocytes: Their Role in Adoptive Immunotherapy. Issue 6 (November 2015) - Noonan, Kimberly A.; Borrello, Ivan M.
Abstract : Abstract: The clinical results achieved with immunotherapy in the past few years have now firmly established it within the cancer armamentarium. Our group has explored a novel approach to adoptive T-cell therapy utilizing marrow-infiltrating lymphocytes (MILs) initially developed with the concept of utilizing a population of T cells with a higher endogenous tumor specificity. Marrow-infiltrating lymphocytes are antigen-experienced T cells that home to and remain in the bone marrow (BM) because of the unique biology of the BM microenvironment. Marrow-infiltrating lymphocytes can easily be obtained from the BM and can be expanded to demonstrate enhanced antigen specificity. Current clinical trials utilize MILs for patients with myeloma as well as patients with relapsed disease following an allogeneic transplant. Ongoing preclinical work is currently evaluating MILs for use in solid cancers as well as pediatric cancers. The examination of a MIL as a source cell for chimeric antigen receptor T or transgenic cell receptor is also in the preclinical stages. Until now, for both chimeric antigen receptor T-cell therapy and transgenic cell receptor T-cell therapy, the target cell of choice has included peripheral blood. The unique antigen-experienced properties of MILs may make them the ideal source of cell for gene modification strategies. Therefore, MILs are a distinctive set of T cells that have been shaped by the unique BM microenvironment and may play a future role as a novel immunotherapy for hematologic malignancies.